Difference between revisions of "2007 BMO Problems/Problem 1"
m |
(→Solution 2) |
||
(One intermediate revision by the same user not shown) | |||
Line 2: | Line 2: | ||
(''Albania'') | (''Albania'') | ||
− | Let <math>ABCD </math> be a convex quadrilateral with <math>AB=BC=CD </math>, <math>AC \ | + | Let <math>ABCD </math> be a convex quadrilateral with <math>AB=BC=CD </math>, <math>AC \neq BD </math>, and let <math>E </math> be the intersection point of its diagonals. Prove that <math>AE=DE </math> if and only if <math> \angle BAD+\angle ADC = 120^{\circ} </math>. |
== Solution == | == Solution == | ||
Line 26: | Line 26: | ||
From these inequalities, we see that <math>\sin (\pi - 2\alpha - \beta ) = \sin (\pi - 2\beta - \alpha) </math> if and only if <math>(\pi - 2\alpha - \beta) = (\pi - 2\beta - \alpha) </math> (i.e., <math>\alpha = \beta </math>) or <math>(\pi - 2\alpha - \beta) + (\pi - 2\beta - \alpha) = \pi </math> (i.e., <math>3(\alpha + \beta) = \pi </math>). But if <math>\alpha = \beta </math>, then triangles <math>ABC, BCD </math> are congruent and <math>AC = BD </math>, a contradiction. Thus we conclude that <math>AE = DE </math> if and only if <math>\alpha + \beta = \pi/3 </math>, Q.E.D. | From these inequalities, we see that <math>\sin (\pi - 2\alpha - \beta ) = \sin (\pi - 2\beta - \alpha) </math> if and only if <math>(\pi - 2\alpha - \beta) = (\pi - 2\beta - \alpha) </math> (i.e., <math>\alpha = \beta </math>) or <math>(\pi - 2\alpha - \beta) + (\pi - 2\beta - \alpha) = \pi </math> (i.e., <math>3(\alpha + \beta) = \pi </math>). But if <math>\alpha = \beta </math>, then triangles <math>ABC, BCD </math> are congruent and <math>AC = BD </math>, a contradiction. Thus we conclude that <math>AE = DE </math> if and only if <math>\alpha + \beta = \pi/3 </math>, Q.E.D. | ||
+ | |||
+ | ==Solution 2== | ||
+ | Let <math><BAC = x</math> and <math><BDC = y</math>. Then by the isosceles triangles manifest in the figure we have <math><DBC = y</math> and <math><ACB = x</math>, so <math><BEA = x+y</math> and <math><EAD = <EDA = \frac{x+y}{2}</math>. Furthermore <math><AEB = 180^\circ - 2x - y</math> and <math><DCE = 180^\circ - x - 2y</math>. | ||
+ | |||
+ | If <math>AE = DE</math>, then <math>BE \neq CE</math>. But also <math>AB = CD</math>, so by SSA "Incongruence" (aka. the Law of Sines: <math>\frac{AE}{\sin <ABE} = \frac{AB}{\sin <BEA} = \frac{CD}{\sin <CED} = \frac{DE}{\sin <ECD}</math>) we have <math><ABE + <DCE = 180^\circ</math>. This translates into <math>180^\circ = 3x + 3y</math>, or <math>120^\circ = 2x + 2y</math>, which incidentally equals <math><BAD + <ADC</math>, as desired. | ||
+ | |||
+ | If <math><BAD + <ADC = 120^\circ</math>, then also <math>x + y + <EAD + <EDA = x + y + (x + y) = 120^\circ</math> by the Exterior Angle Theorem, so <math>3x + 3y = 180^\circ</math> and hence <math><ABE</math> and <math><DCE</math> are supplementary. A simple Law of Sines calculation then gives <math>AE = DE</math>, as desired. This completes both directions of the proof. | ||
+ | |||
Latest revision as of 22:59, 14 September 2014
Contents
Problem
(Albania)
Let be a convex quadrilateral with
,
, and let
be the intersection point of its diagonals. Prove that
if and only if
.
Solution
Since ,
, and similarly,
. Since
, by considering triangles
we have
. It follows that
.
Now, by the Law of Sines,
.
It follows that if and only if
.
Since ,
![$0 < (\pi - 2\alpha - \beta) + (\pi - 2\beta - \alpha) < 2\pi$](http://latex.artofproblemsolving.com/1/3/1/1316ab62513fdc1d1efe0447b00bb009c900e03c.png)
and
![$-\pi < (\pi - 2\alpha - \beta) - (\pi - 2\beta - \alpha) < \pi$](http://latex.artofproblemsolving.com/9/3/d/93da4b1ff91cea97dfd30ea7ef9472f62f689bd4.png)
From these inequalities, we see that if and only if
(i.e.,
) or
(i.e.,
). But if
, then triangles
are congruent and
, a contradiction. Thus we conclude that
if and only if
, Q.E.D.
Solution 2
Let and
. Then by the isosceles triangles manifest in the figure we have
and
, so
and
. Furthermore
and
.
If , then
. But also
, so by SSA "Incongruence" (aka. the Law of Sines:
) we have
. This translates into
, or
, which incidentally equals
, as desired.
If , then also
by the Exterior Angle Theorem, so
and hence
and
are supplementary. A simple Law of Sines calculation then gives
, as desired. This completes both directions of the proof.
Alternate solutions are always welcome. If you have a different, elegant solution to this problem, please add it to this page.